RANCANGAN PENGGUNAAN SEL SURYA UNTUK MEMENUHI SEBAGIAN KEBUTUHAN LISTRIK PERUMAHAN (STUDI KASUS PERUMAHAN PARADISE, SLEMAN, DIY) - , RAMA GAMARA TOLONGAN; , Rachmawan Budiarto S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Unrenewable energy use such as oil to generate electricity start to meets some barriers, Indonesia dan world oil reserve depleting, and its carbondioxide exhaust that causing greenhouse effect. To solve this problem then energy diversification should be done to generate electricity using renewable source, which one using solar cell. This study was conducted to determine the potential energy, getting the design and conduct technical and economic feasibility analysis of the design of the use of solar cells as a power plant to meet some of the power needs of Paradise residence, Sleman, Yogyakarta. The study started by collecting residential electricity consumption data, using questionnaires and then look for secondary data such as power and specification of the corresponding solar cells. After that, the calculation performed using Ms.Excel software. Calculation results are then analyzed so that conclusions can be drawn in the form of potential energy, economic value and feasibility of the design of the use of solar cells as a power plant to meet the some power needs of the residential. The system designed to meets the power needs of 42.97 kWh per day using 48 solar modules, connected up to 3 parallel and a maximum of 12 connections series, and connected to the grid. Economic calculations show that the cost of electricity is Rp 1.617,92 for each kilowatt-hour that is supplied by the solar power system.